(untitled) (Research, Society and Development, 2022)
Temporomandibular joint dysfunction (TMD) is a problem related to oral health that can have different origins and forms of manifestation in the individual. Many health professionals, especially dentists, have used acupuncture in the treatment of TMD to reduce pain and severity. Given the above, this research aims to analyze from the literature review the importance of acupuncture in the treatment of Temporomandibular Disorders. As for the methodological process, it was adopted as the objective, data collection and analysis of results, respectively, descriptive research, bibliographical and content analysis. Scientific productions on the importance of acupuncture in the treatment of TMD reveal that this ancient Chinese technique has the ability to reduce pain, relax muscles and minimize the severity of the pathology. It is concluded that acupuncture is as efficient as other more invasive procedures in the treatment of TMD, however, it is still little explored by health professionals.